2015
DOI: 10.1007/s10730-014-9263-3
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Experiences of Community Members Serving on Institutional Review Boards: A Questionnaire Based Study

Abstract: The community representative plays a very important role in an institutional review board (IRB) but there is sparse data about their understanding of their role in an IRB. This study was conducted to assess perceptions of community members serving on IRBs of one region in India. A validated questionnaire (Cohen's kappa coefficient of 0.84) was administered to community members of IRBs in a prospective cross-sectional study. The questions related to demography, perceptions of their role in the IRB, experiences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 6 publications
1
7
0
1
Order By: Relevance
“…These findings emphasize the need for an increase in basic training with development of modules including those available online. 10…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings emphasize the need for an increase in basic training with development of modules including those available online. 10…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in a study of Indian board members, Kuyare et al. 10 suggested that being experienced may actually be counterproductive to the role of non-specialist members as participant/community representatives. That is, the more experience they gain, the more knowledgeable they become and therefore the less able they are to represent the community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A survey among laypersons serving on ECs revealed several of them did not review informed consent documents (ICDs), those who said they did not understand technical terms in the ICDs, and one-third were unaware that their presence was vital for quorum to be met. [ 21 ] Other papers have also identified the lack of active participation of nonmedical members in the Committee's deliberations, as well as the fact that they lack training and are diffident. [ 22 23 ]…”
Section: The Past (2005–2013)mentioning
confidence: 99%
“…Introducción L a figura del representante en la comunidad (RC), en los Comités de Ética en Investigación o Comités Institucionales de Ética (CEI) o juntas de revisión institucional (IRB en sus siglas en inglés) ha sido, en general, poco comprendida (Kuyare 2015). Muchos CEI tienen a esas personas solo porque es una exigencia de la reglamentación vigente y por tanto su elección, capacitación y funcionamiento no están en las prioridades de los directivos de las instituciones o de los CEI 1 .…”
Section: Palavras-chave Comitês De éTica Em Investigação Investigaçãunclassified